Complete Revascularization with Multivessel PCI for Myocardial Infarction - Mehta, Shamir R; Wood, David A; Storey, Robert F; Mehran, Roxana; Bainey, Kevin R; Nguyen, Helen; Meeks, Brandi; Di Pasquale, Giuseppe; López-Sendón, Jose; Faxon, David P; Mauri, Laura; Rao, Sunil V; et al. (My University, 2019)
In patients with ST-segment elevation myocardial infarction (STEMI), percutaneous coronary intervention (PCI) of the culprit lesion reduces the risk of cardiovascular death or myocardial infarction. Whether PCI of nonculprit lesions further reduces the risk of such events is unclear.